STUDY OF SUPEROXIDE DISMUTASE AND MALONDIALDEHYDE CONCENTRATIONS IN MICE AFTER ADMINISTRATION OF METHANOLIC EXTRACT of Scurrula atropurpurea (BL.) - Athiroh, Nour; Wahyuningsih, Doti (Universitas Syiah Kuala, 2017)
The aim of this research was to investigate the potential effect of methanolic extract of Scurrula atropurpurea (MESA) in reducing oxidative stress through observation of superoxide dismutase (SOD) activity and malondialdehyde (MDA) concentration in mice. In this research, 25 male mice were divided into four groups with five replications. Group I (K1, without MESA) was considered as a control group, while Group II (K2), III (K3), and IV (K4) were given 1000, 2000, and 4000 mg MESA/kg BW, respectively. After 14 days, SOD activity and MDA concentration were measured spectrophotometrically. The SOD activity did not significantly increased (P0.05) in group K1, K2, K3, and K4 with values were 19.4692.072, 17.41.373, 20.533.411, and 23.872.528 U/ml, respectively. In contrast, MDA concentration was decreased (P0.05) with values of 492.75019.418, 492.75019.418, 457.12530.095, 454.62519.080, and 475.87537.659 ng/mL in groups K1, K2, K3, and K4, respectively. It can be concluded that the administration of MESA tend to increase SOD activity and decrease MDA concentration in this study, thus might be able to reduce oxidative stress in mice.